2019
DOI: 10.1155/2019/2018374
|View full text |Cite
|
Sign up to set email alerts
|

How Many Patients with Type 2 Diabetes Meet the Inclusion Criteria of the Cardiovascular Outcome Trials with SGLT2 Inhibitors? Estimations from a Population Database in a Mediterranean Area

Abstract: Objective Regulatory agencies require the assessment of cardiovascular (CV) safety for new type 2 diabetes (T2D) therapies through CV outcome trials (CVOTs). However, patients included in CVOTs assessing sodium-glucose cotransporter-2 inhibitors (SGLT2i) might not be representative of those seen in clinical practice. This study examined the proportion of patients that would have been enrolled into three main SGLT2i CVOTs to determine whether these trials' eligibility criteria can be applied to a real-world Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…Our findings are in line with those from previous studies in Catalonia, the US, and the UK, which reported that only 8.2%, 4.1%, and 15.7% of patients with diabetes, respectively, met eligibility criteria for EMPA-REG OUTCOME. [ 21 , 37 , 38 ] Previous studies [ 21 , 39 ] found that over 80% and 90% of new users of SGLT-2 inhibitors, respectively, would not have been eligible for the EMPA-REG OUTCOME trial. These findings suggest that most clinical decision-making is not based on the direct interpretation of this pragmatic RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with those from previous studies in Catalonia, the US, and the UK, which reported that only 8.2%, 4.1%, and 15.7% of patients with diabetes, respectively, met eligibility criteria for EMPA-REG OUTCOME. [ 21 , 37 , 38 ] Previous studies [ 21 , 39 ] found that over 80% and 90% of new users of SGLT-2 inhibitors, respectively, would not have been eligible for the EMPA-REG OUTCOME trial. These findings suggest that most clinical decision-making is not based on the direct interpretation of this pragmatic RCT.…”
Section: Discussionmentioning
confidence: 99%
“…A further limitation is related to the patient characteristics used in the model. This analysis assumed that patient profile of the Spanish population with T2DM in clinical practice was similar to that of the patients in the DECLARE-TIMI 58 trial, but published evidence shows that around 38% and 51% of patients treated with dapagliflozin in clinical practice met the inclusion criteria for the DECLARE-TIMI 58 trial [ 19 , 47 ]. However, univariate sensitivity analyses were carried out, in which baseline characteristics (age and eGFR) were modified, and a PSA were also performed to ensure the representativeness of T2DM patients who may be treated with dapagliflozin in real clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Eligibility requirements for study participation usually include having a history of cardiovascular disease or high cardiovascular risk in addition to certain age and blood glucose control specifications. According to estimates from population-based data, only 4% to 38% of the real-world population with type 2 diabetes would have qualified for enrollment into renowned CVOTs [ 21 23 ]. Moreover, as pointed to by Lipska/Krumholz [ 24 ], CVOTs would probably not be very informative for the present study question, because the study protocols of the CVOTs in general encourage additional glucose control according to the local guidelines.…”
Section: Discussionmentioning
confidence: 99%